The altered TBI fecal microbiome is stable and functionally distinct - Pyles, Richard B.; Miller, Aaron L.; Urban, Randall J.; Sheffield-Moore, Melinda; Wright, Traver J.; Maxwell, Carrie A.; Randolph, Kathleen M.; Danesi, Christopher P.; McGovern, Kristen A.; Vargas, Jayson; Armstrong, Peyton; Kreber, Lisa; et al. (Frontiers in Molecular Neuroscience, 2024)
Introduction Patients who suffer a traumatic brain injury (TBI) often experience chronic and sometimes debilitating sequelae. Recent reports have illustrated both acute and long-term dysbiosis of the gastrointestinal microbiome with significant alterations in composition and predicted functional consequences. Methods Working with participants from past research, metagenomic stability of the TBI- associated fecal microbiome (FMB) was evaluated by custom qPCR array comparing a fecal sample from 2015 to one collected in 2020. Metatranscriptomics identified differently expressed bacterial genes and biochemical pathways in the TBI FMB. Microbiota that contributed the largest RNA amounts identified a set of core bacteria most responsible for functional consequences of the TBI FMB. Results A remarkably stable FMB metagenome with significant similarity (two-tail Spearman nonparametric correlation p < 0.001) was observed between 2015 and 2020 fecal samples from subjects with TBI. Comparing the 2020 TBI FMB metagenome to FMBs from healthy controls confirmed and extended the dysbiotic genera and species. Abundance differences between average TBI and healthy FMBs revealed Bacteroides caccae, B. uniformis, Blautia spp., Collinsella spp., Dialister spp., and Ordoribacter spp. were significantly different. Functionally, the Parabacteroides genus contributed the highest percentage of RNA sequences in control FMBs followed by the Bacteroides genus as the second highest contributor. In the TBI FMB, the Corynebacterium genus contributed the most RNA followed by the Alistipes genus. Corynebacterium and Pseudomonas were distinct in the top 10 contributing genera in the TBI FMB while Parabacteroides and Ruminococcus were unique to the top 10 in controls. Comparing RNA profiles, TBI samples had ∼1.5 fold more expressed genes with almost 700 differently expressed genes (DEGs) mapped to over 100 bacterial species. Bioinformatic analysis associated DEGs with pathways led identifying 311 functions in the average TBI FMB profile and 264 in the controls. By average profile comparison, 30 pathways had significantly different abundance (p < 0.05, t-test) or were detected in >80% of the samples in only one of the cohorts (binary distinction). Discussion Functional differences between TBI and healthy control FMBs included amino acid metabolism, energy and carbon source usage, fatty acid metabolism, bacterial cell wall component production and nucleic acid synthesis and processing pathways. Together these data shed light on the functional consequences of the dysbiotic TBI FMB decades after injury.